2019
DOI: 10.1186/s12967-019-2052-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling trauma in rats: similarities to humans and potential pitfalls to consider

Abstract: Trauma is the leading cause of mortality in humans below the age of 40. Patients injured by accidents frequently suffer severe multiple trauma, which is life-threatening and leads to death in many cases. In multiply injured patients, thoracic trauma constitutes the third most common cause of mortality after abdominal injury and head trauma. Furthermore, 40–50% of all trauma-related deaths within the first 48 h after hospital admission result from uncontrolled hemorrhage. Physical trauma and hemorrhage are freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 194 publications
(230 reference statements)
1
51
0
5
Order By: Relevance
“…One of the limitations of this model is that only minimal results concerning wound healing can be ascertained since it only extends till the very early stages of healing (if at all). Rats utilize contraction for wound closure, which typically minimizes risks of infection and/or sepsis (Abdullahi et al, 2014;Weber et al, 2019). That said, some re-epithelization and granulation tissue was noted by the pathologist, particularly in the DPT burn wounds (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the limitations of this model is that only minimal results concerning wound healing can be ascertained since it only extends till the very early stages of healing (if at all). Rats utilize contraction for wound closure, which typically minimizes risks of infection and/or sepsis (Abdullahi et al, 2014;Weber et al, 2019). That said, some re-epithelization and granulation tissue was noted by the pathologist, particularly in the DPT burn wounds (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Models involving larger burns (i.e., greater TBSA) and bacterial infection typically have a shorter time course or result in high mortality of the animals. A lower TBSA, coupled with the rapid diversification between rat and human immune systems, may explain the minimal effects seen in systemic responses (Weber et al, 2019). While we did see cases of sepsis, typically in the FT burns, animals survived the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Their beneficial effects in trauma can be summarized as migration and integration into the site of injury and respond to immunostimulatory molecules defined as damage-associated molecular patterns. Besides, they generate an anti-inflammatory and pro-regenerative microenvironment through secreting factors that activate the growth and differentiation of adjacent cells, stimulate angiogenic activity, regulate functions of endothelial cells and fibroblasts, and inhibit fibrosis [ 25 ]. A previous systematic review and meta-analysis study investigating the efficacy of MSC transplantation in animal models of TBI suggested that MSCs might have beneficial effects on locomotor recovery [ 26 ].…”
Section: Traumamentioning
confidence: 99%
“…However, it is worth-mentioning that, although small animal models are commonly used for wound healing research, they display some biological limitations due to the differences in the histological architecture of rodent vs. human skin, and in the primary physiological act of healing, i.e., myofibroblast contraction for rodents vs. re-epithelization for humans. Other experimental models, such as the porcine one, have been proven to be more linkable with the human healing process, but the costs of housing and the difficulties in handling have limited their usability for first-line exploratory research [23,24]. Another aspect to consider is that "pure" scarring-free regeneration, which only sees new cells completely replacing the lost ones, is very uncommon in humans.…”
Section: Introductionmentioning
confidence: 99%